-7(x-9)=-56

Simple and best practice solution for -7(x-9)=-56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x-9)=-56 equation:


-7(x-9)=-56

We simplify the equation to the form, which is simple to understand
-7(x-9)=-56

Reorder the terms in parentheses
+(-7x+63)=-56

Remove unnecessary parentheses
-7x+63=-56

We move all terms containing x to the left and all other terms to the right.
-7x=-56-63

We simplify left and right side of the equation.
-7x=-119

We divide both sides of the equation by -7 to get x.
x=17

See similar equations:

| x+4.6=6.9 | | 18p=-11 | | 63+7x+12=180 | | -4.7=c+4.5 | | 9x-9=70 | | 9x-9x=70 | | 1.50x+19.00=2.75x+15.00 | | 6y-y=3 | | 9x=70 | | -2.7d=10.8 | | x-9=70 | | 2x=1.3 | | -551-(-1056)= | | x+x-9=70 | | (5x+8)+(9y+1)=180 | | 10=-3.2+r | | 50+60x=20+75x | | 45%800= | | -17+14=m-10 | | 2(4+1)=9 | | X-2=4(x-2) | | 2+8x=19+x | | j^3k^6= | | -50.4=4.2f | | 2(4x+1)= | | (5x-2)=2 | | j^3k^5= | | 3(x-1)-8=14-2(3x-4) | | x+2x+1=13 | | 7p+2p+9p-2= | | j^2k^2= | | 4v^2+4=7 |

Equations solver categories